Laparoendoscopic single-site repair of retrocaval ureter without any special devices - Rebouças, Rafael B. (2013)
The retrocaval ureter is a rare congenital anomaly. The extrinsic compression may be responsible for obstruction and pain symptoms. The laparoscopic approach has been used with good results and less morbidity than the open surgery. Herein we describe a case of retrocaval ureter treated with LESS. To our knowledge, this represents the second such case reported in the literature, and the first without using any special devices, such as, single port or bended instruments. PRESENTATION Female, 23 years, complaining of right low back pain for a long time and recurrent urinary tract infection. Renal ultrasound demonstrated right-sided hydronephrosis and intravenous urography suggested the presence of retrocaval ureter. DTPA renal scintigraphy confirms delay in the elimination of contrast through the right kidney. A laparoendoscopic single-site repair was planned. The patient was placed in rightside-up modified flank position. A semicircular intra-umbilical incision was made and the conventional trocars (one 10 mm and two 5 mm) were inserted through the same incision on different points of the aponeurosis. The colon was dissected medially and the proximal ureter lateral to the vena cava was identified and dissected. An extra corporeal repair with Vycril 2-0 was used to facilitate the ureteral dissection and the anastomosis. A segment of ureter was ressected due to the tortuosity. Two 4-0 Vycril sutures were used to perform a running anastomosis. An ureteral stent was placed after the posterior layer on an antegrade fashion. A suction drain was left through the umbilicus. RESULTS The total operative time was 145 min. The blood loss was minimal. The patient was discharged on the third postoperative day and resumed total activity about 10 days after surgery. The double J was removed within 4 weeks. DISCUSSION Albeit technically challenging, LESS repair for retrocaval ureter might represent a feasible new treatment option for this rare anatomic anomaly. Special devices could help on the procedure, however they are not essencials.